2017
DOI: 10.1002/jms.3929
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of fluvastatin metabolites in rats by UHPLC/Q‐TOF/MS/MS and in silico toxicological screening of the metabolites

Abstract: The present study reports the in vivo and in vitro identification and characterization of metabolites of fluvastatin, the 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase inhibitor, using liquid chromatography-mass spectrometry (LC-MS). In vitro studies were conducted by incubating the drug with human liver microsomes and rat liver microsomes. In vivo studies were carried out by administration of the drug in the form of suspension to the Sprague-Dawley rats followed by collection of urine, faeces and blood at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The accurate masses of these two metabolites were m/z 420.2623 and m/z 420.2623 as shown in the MS/MS spectra in Figure 1b,c. The elemental composition of C 21 H 34 N 5 O 4 + indicates that there is a loss of two carbons and three fluorine atoms, suggesting that these metabolites were formed by the hydrolysis of an amide bond followed by hydroxylation (Chavan et al, 2017). The observed metabolic change was justified by the fragmentation pattern, which is as follows (Figure 5): as per the MS/MS spectrum, M1 initially dissociated to two product ions, namely, m/z 402 on the loss of H 2 O and m/z 307 on the loss of C 6 H 11 NO.…”
Section: Resultsmentioning
confidence: 99%
“…The accurate masses of these two metabolites were m/z 420.2623 and m/z 420.2623 as shown in the MS/MS spectra in Figure 1b,c. The elemental composition of C 21 H 34 N 5 O 4 + indicates that there is a loss of two carbons and three fluorine atoms, suggesting that these metabolites were formed by the hydrolysis of an amide bond followed by hydroxylation (Chavan et al, 2017). The observed metabolic change was justified by the fragmentation pattern, which is as follows (Figure 5): as per the MS/MS spectrum, M1 initially dissociated to two product ions, namely, m/z 402 on the loss of H 2 O and m/z 307 on the loss of C 6 H 11 NO.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of uorescence detection with extraction using hydrophobic deep eutectic solvents (DES) for the analysis of studied drugs offers several advantages over traditional techniques such as high-performance liquid chromatography (HPLC), [15][16][17][18][19][20] electrochemical techniques, [21][22][23] and spectroscopic methods. [24][25][26][27][28][29] Firstly, uorescence detection provides high sensitivity and selectivity, allowing for the detection and quantication of drugs at low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies involving microsomal enzymes and in vivo animal studies are usually applied to understand drug metabolism 3 . In recent times, the site of metabolism has been predicted through in silico studies and probable structures of metabolites are being identified quickly by hyphenated techniques like liquid chromatography/high‐resolution mass spectrometry (LC/HRMS) 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…3 In recent times, the site of metabolism has been predicted through in silico studies and probable structures of metabolites are being identified quickly by hyphenated techniques like liquid chromatography/high-resolution mass spectrometry (LC/HRMS). [4][5][6] Arterolane (ART) is reported as one of the fast-acting schizonticides at the erythrocytic stages of the malaria parasite which is being approved in India to treat plasmodium-associated malaria.…”
Section: Introductionmentioning
confidence: 99%